Scientiae Educatia: jurnal pendidikan sains (2012)
Scientiae Educatia [p-ISSN 2303-1530| e-ISSN 2527-7596] publishes a scientific paper on the result of the study and review of the literature in sphere of natural sciences education and natural sciences. This journal collaborates with Perkumpulan Pendi
dik IPA Indonesia (PPII) / Indonesian Society for Science Educators